new digital age reshaping the future of people, nations and business - Schmidt Eric. (New York Jojn Murray, 2013)
From two leading thinkers, the widely anticipated book that describes a new, hugely connected world of the future, full of challenges and benefits which are ours to meet and harness. The New Digital Age is the product of an unparalleled collaboration: full of the brilliant insights of one of Silicon Valley's great innovators - what Bill Gates was to Microsoft and Steve Jobs was to Apple, Schmidt (along with Larry Page and Sergey Brin) was to Google - and the Director of Google Ideas, Jared Cohen, formerly an advisor to both Secretaries of State Condoleezza Rice and Hillary Clinton.
Includes bibliographical references (pages 263-301) and index
Keywords: Digital electronics--Social aspects--Forecasting.